Retrofitting of interior RC beam–column joints using CFRP strengthened SHCC: Cast-in-place solution - Esmaeeli, Esmaeel (2015)
The effectiveness of a repair strategy, for damaged RC beam–column joints, that combines strain hardening cementitious composite (SHCC) and laminates of carbon fiber reinforced polymers (CFRP laminates) is assessed in the present work. According to this technique, the existing concrete cover in the joint zone of the frame is replaced by a self-compacting SHCC. This thin layer of SHCC is reinforced with CFRP laminates that are bonded into the saw cut grooves. Two full-scale severely damaged interior RC beam–column joints were retrofitted using two different configurations of this technique: (i) applying the strengthening system to only the front and rear faces of the specimen; (ii) jacketing all sides of the elements of the specimen with the strengthening system. The effectiveness of these retrofitting configurations is assessed and compared by evaluating experimentally the hysteretic response, the dissipated energy, the degradation of secant stiffness, the displacement ductility and the failure modes of each repaired specimen, and also using the values of these indicators obtained in the virgin state of the specimens. This comparison revealed that the adopted retrofitting strategies can restore and even enhance the performance of this type of structural elements, mainly when the solution based on four-sided jacketing is used.